Overview of Environmental Management Practice for Construction in Malaysia - Teng Wen Chang; Dilip Kumar (Tecno Scientifica Publishing, 2021)
The surrounding environment plays an important role in communities as living in a good environment can improve the health cycle, increase the quality of life and provide sustainable development for the country. The rapid growth of the human population has led to the increasing demand for infrastructure development and the construction sector in Malaysia. This overview of environmental management practice for construction in Malaysia has reviewed the overall structure of environmental management for the construction site in Malaysia. Construction management is covered in this review report, including construction waste generation, construction waste management, government bodies, government policy, the current status of the environment in Malaysia, challenges, future prospects, and other environmental considerations of environmental management practice for construction in Malaysia. Besides, the detailed guideline and orders for construction waste, effluence discharge, noise pollution, vibration, and emission release from construction in Malaysia have been reviewed and stated in this report. Lastly, a recommendation for strengthening the enforcement of law and regulation for environmental management practice to comply has been included in the conclusion of this report to overcome the challenges faced for sustainable construction development in Malaysia.